Defining precision health: a scoping review protocol - Jillian C Ryan; John Noel Viana; Hamza Sellak; Shakuntla Gondalia (BMJ Open, 2021)
Introduction Precision health is a nascent field of research that would benefit from clearer operationalisation and distinction from adjacent fields like precision medicine. This clarification is necessary to enable precision health science to tackle some of the most complex and significant health problems that are faced globally. There is a pressing need to examine the progress in human precision health research in the past 10 years and analyse this data to first, find similarities and determine discordances in how precision health is operationalised in the literature and second, identify gaps and future directions for precision health research.Methods and analysis To define precision health and map research in this field, a scoping review will be undertaken and reported according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses - Scoping Review Extension guidelines. Systematic searches of scientific databases (Medline, Embase, Scopus, Web of Science and PsycINFO) and grey literature sources (Google Scholar, Google Patents) identified 8053 potentially eligible articles published from 1 January 2010 to 30 June 2020. Following removal of duplicates, a total of 3190 articles were imported for screening. Article data will be extracted using a customised extraction template on Covidence and analysed descriptively using narrative synthesis.Ethics and dissemination Ethics approval is not required. Findings will be disseminated through professional networks, conference presentations and publication in a scientific journal.